The need and structural elements of continuous support of small businesses - Rajabov Utkir Dusnayevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the importance of small business and private entrepreneurship in the sustainable development of the country’s economy and in meeting the endlessly growing needs of the population. the need for state regulation and conditions for guaranteeing private property and creating an attractive investment environ ment are analyzed.